Development of a framework for the management of risk for SME’s in South Africa that outsource some, or all, of their manufacturing requirements - Walters, Michael Graham (My University, 2020)
Small companies routinely outsource their payroll processing, accounting, distribution, and many other important functions - often because they have no other choice. Similarly, manufacturing SMEs (mSMEs) may choose to outsource some of their manufacturing to a local agent. This strategy can realise many benefits, but these are weighed against heavy risks. This research investigated the major benefits, risks and risk management strategies in industry through in-depth, semi-structured interviews of the owner-managers of four selected local mSMEs. The results were then analysed using thematic analysis techniques and compared to those found in literature, ending in an emergent conceptual framework and a suggested approach for owner manager to the topic. The key benefits South African mSMEs seek when outsourcing manufacturing area reduction in capital and operational expenses, decreased time to market and the ability to focus on their core competencies. South African mSMEs do not outsource in order to gain increased flexibility. The major risks they are exposed to can be grouped into quality, time/speed, financial and legal based risks. There is little knowledge transfer from literature to industry with regards to risk management. South African mSME owner-managers approach to this has, however, evolved through experience to a point where it closely mirrors suggested best practices. They employ multiple strategies that fall within risk avoidance, control, assumption and transfer categories. Of note in South Africa is the importance of the relationship between the principal and agent as this facilitates and enhances all aspects of risk management for local outsourced manufacturing
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2020